Ab initio studies of two Al grain boundaries subjected to mixed tension/shear mode loading: how shear may promote breakage. (13th June 2017) - Ehlers, F J H; Seydou, M; Tingaud, D; Maurel, F; Queyreau, S; Charles, Y
Abstract: Using the framework of density functional theory, the structural and energetic response of two face-centred cubic (fcc) Al grain boundaries (GBs) to combined tension and shear loadings has been examined. It is shown that tension will serve to inhibit the Σ5 [100] 36.87° twist GB response to shear in a mixed-mode loading scenario, by increasing the difference in structural environments for inequivalent atoms at the GB plane. We propose that the presence of such atoms, rather than the full structural details of the GB structure, is instrumental in triggering this tension–shear interplay. As support for this hypothesis, we compute the Σ3 [-110] (111) 60° symmetric tilt GB mixed-mode loading response. Here, all atoms at the GB plane are equivalent, and the qualitative shear energy variation is unaffected by tension. Our findings indicate that general fcc Al GBs may display a stronger shear energy variation at larger levels of tension, contrasting general expectations. The implications to GB breakage are discussed.